Inequality, Poverty, and Growth : Cross-Country Evidence - Iradian, Garbis (IMF Working Papers; Working Paper ;, 2005)
This paper examines the empirical relationship between inequality and growth, and analyzes the impacts of growth, inequality, and government spending on poverty reduction. A new panel dataset has been assembled on inequality and poverty that reduces measurement error and ensures comparability across countries and over time. The empirical results in this paper challenge the belief that income inequality has a negative effect on growth and confirm the validity of the Kuznets curve. Credit market imperfections in low- and medium-income countries are identified as the likely reason for the positive link between inequality and growth over the short-to-medium term. In the long term, inequality may have an adverse impact on growth.